A sustainable low temperature yarn reinforcing process to reduce water and energy consumptions and pollution in the textile industry. (10th February 2019) - Jiang, Qiuran; Chen, Si; Deng, Xiong; Feng, Yani; Reddy, Narendra; Zhu, Quan; Liu, Wanshuang; Qiu, Yiping
Abstract: Conventional weaving processes usually require sizing and desizing treatments, which incur additional costs, water and energy consumptions and also cause environmental pollution. These issues suppress the development of the essential but low-margin textile industry. In this research, a low temperature alkaline treatment was developed to reinforce pure cellulose or cellulose blended warp yarns with the low molecular weight components directly dissolved from yarns. This treatment eliminates the need for the conventional sizing and desizing processes, leading to substantial reduction in the water pollution and the consumptions of water and energy. The morphology, hairiness, chemical structure, crystallinity, mechanical properties, abrasion resistance, dyeability and weavability of the yarns after the low temperature alkaline treatment were investigated in comparison to starch and starch/poly (vinyl alcohol) sized yarns. The results indicated that this new treatment could permanently remove 94% harmful hairiness of warps, provide comparable reinforcement in the tenacity (31% enhancement), abrasion resistance (27 cycles), and better retention in elongation (6%) and enhanced dyeability (92% higher in K/S value). Notably, the fabrics with the treated warps did not require any desizing process and showed similar softness compared to the desized fabrics. Taking into account the low cost, short process, reduced water and energy consumptions and less pollution, this new approach of warp treatment has great potential to promote sustainability and environmentally friendly processing in the textile industry. Graphical abstract: Highlights: A low temperature treatment to replace the conventional warp yarn sizing process. Improved qualities with preserved elongation, enhanced strength and dyeability. The 11-step procedure for fabric production simplified to an 8-step procedure. A competitive procedure with reduced costs, water/energy consumption and pollution.